1997
DOI: 10.1007/s001040050360
|View full text |Cite
|
Sign up to set email alerts
|

Der longitudinale Muskel des Analkanals The anal longitudinal muscle

Abstract: The longitudinal muscle (LM) represents a strong muscular structure of the anal canal situated between the internal (IAS) and the external anal sphincter (EAS). Terminal fibres of this muscle insert at the submucosa of the anal canal, representing the m. canalis ani. Others cross the subcutaneous part of the EAS to become the m. corrugator ani. Thus, the LM connects the visceral and somatic parts of the anal sphincter complex. Histologically ganglionic cells and as Vater-Pacinian corpuscles can be identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
3
1
Order By: Relevance
“…Our study confirms the intersphincteric location of the LAM, interposed between IAS and EAS, with mean thicknesses of 1.63 mm (LAM), 2.69 mm (IAS), and 2.95 mm (EAS). These data partially fit those of Gerdes et al, 22 who reported a mean thickness of the LAM of 2.85 mm and of the EAS of 3.62 at the level of the dentate line. These differences may be ascribed to different fixation and level of section.…”
Section: Discussionsupporting
confidence: 88%
“…Our study confirms the intersphincteric location of the LAM, interposed between IAS and EAS, with mean thicknesses of 1.63 mm (LAM), 2.69 mm (IAS), and 2.95 mm (EAS). These data partially fit those of Gerdes et al, 22 who reported a mean thickness of the LAM of 2.85 mm and of the EAS of 3.62 at the level of the dentate line. These differences may be ascribed to different fixation and level of section.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to other authors (Swash et al, 1988;Lowry, 1992;Lunniss and Phillips, 1992;McMinn, 1992;Fleshman, 1993;Gerdes et al 1997), we found that the internal anal sphincter muscle rings do not share the same fascia as the longitudinal fibromuscular band and that they could be easily dissected from each other. Because this fascial separation has heretofore been unappreciated, the ring-like structures of the internal anal sphincter have not been described in classic textbooks and in more recent studies.…”
Section: Discussioncontrasting
confidence: 82%
“…Mechanical insult to the internal anal sphincter may result in bowel incontinence. These insults may be surgical (e.g., fissurectomy, fistulotomy, and sphincterotomy), obstetrical (e.g., third-or fourth-degree tears of the perineum during delivery), or traumatic (e.g., blunt trauma, impalement, gunshot wounds, or foreign-body insertion) (Cherry and Greenwald, 1992;Lowry, 1992;Schrock, 1996;Gerdes et al, 1997;Corman, 1998). Because of its clinical significance in ensuring bowel continence, the structure and function of the internal anal sphincter should be thoroughly investigated and understood.…”
Section: Introductionmentioning
confidence: 98%
“…Lunniss and Phillips 23 and Gerdes et al 24 have independently investigated the anal longitudinal muscle and discussed its intersphincteric position in the rectal wall, demonstrating it both anatomically and by endoanal ultrasonography. Our group has also previously confirmed its presence in over two-thirds of patients assessed, using endoanal magnetic resonance imaging, where, on T1-weighted and T2-weighted images, it appears as a thin layer of beaded intermediate to low signal intensity running parallel to the anal canal.…”
Section: Discussion and Clinical Relevancementioning
confidence: 99%